2021
DOI: 10.1111/1462-2920.15407
|View full text |Cite
|
Sign up to set email alerts
|

How multiple farming conditions correlate with the composition of the raw cow's milk lactic microbiome

Abstract: Questionnaires on farming conditions were retrieved from 2129 dairy farms and clustered, resulting in 106 representative raw cow's milk samples analysed in winter and summer. Substantiating the efficiency of our survey, some farming conditions affected the milk physicochemical composition. Culturing identified several species of lactic acid bacteria (LAB) per milk, whose number increased through 16S ribosomal RNA (rRNA) gene sequencing and shotgun metagenome analyses. Season, indoor versus outdoor housing, cow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…In addition, our data showed a significantly higher abundance of Limosilactobacillus fermentum in summer milk. In agreement, other studies have reported an enrichment of LAB genera during the hot season ( 15 , 20 , 54 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In addition, our data showed a significantly higher abundance of Limosilactobacillus fermentum in summer milk. In agreement, other studies have reported an enrichment of LAB genera during the hot season ( 15 , 20 , 54 ).…”
Section: Discussionsupporting
confidence: 92%
“…As the convergent result of a multitude of abiotic and biotic factors having a stochastic, deterministic, and temporary impact on the microbiota ( 2 , 3 , 15 , 20 ), milk has been recognized as one of the most complex and unpredictable food matrices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the majority of cheeses are produced from cow’s milk, cheese from sheep, goats, buffalo, camels, and even donkeys is manufactured [ 43 ]. Genera common to all raw milk include Lactococcus , Lactobacillus , Leuconostoc , Streptococcus , and Enterococcus , although certain varieties are more strongly associated with one type or another, which impacts the microbiome of a final product [ 44 , 45 , 46 ]. For example, while the predominant genera in cow’s milk include Pseudomonas , Bacillus , Lactococcus , and Acinetobacter , the genera most common to raw camel’s milk include Enterococcus , Lactococcus , and Pediococcus [ 47 , 48 ].…”
Section: Fermented Foodmentioning
confidence: 99%
“…However, the bacterial flora in raw milk collected in tanks on farms after milking is affected by the season, farm environment, cow hygiene and rearing environment, and storage conditions of raw milk. Lactobacillus delbrueckii evaluated in this study was isolated from milk sampled from a tank in a milk plant, and its flora may be influenced by various factors (Hagi et al, 2010;Hagi et al, 2013;Cao et al, 2021;Hornik et al, 2021;Nikoloudaki et al, 2021).…”
Section: Distribution Of Mlsa Clusters (Subspecies) Among the 226 Str...mentioning
confidence: 99%